Iran-Saudi Arabia Diplomatic Relations and China's Role in Regional Politics - MUHAMMAD BILAL; Sajida Begum; Amina Farooq (National University of Modern Languages (NUML), Islamabad, 2024)
This article examines the latest diplomatic developments between Saudi Arabia and Iran and China's role in regional politics. The study explores the historical context of these nations' harsh diplomatic relations and the different concerns that have pursued the latest diplomatic warmth. Moreover, it explores China's enhancing engagement in the Middle East, specifically its growing financial and strategic relations with Saudi Arabia and Iran, and the impression of this on regional political order. This research is the result of an analysis of both primary and secondary sources, involving official data, and academic and media reports. The results suggest that the improvising relations between Saudi Arabia and Iran have the courage to incorporate stability into International Politics, while China's contribution to regional order can give a new arena for support and development. This article yields with recommendations for relevant stakeholders and political actors in leading stability and peace in the Gulf.